(untitled) (International Journal of Ayurveda and Pharma Research, 2019)
Menstruation is normal vaginal bleeding that occurs every month in all women of reproductive age group (15-49yrs). According to Ayurveda, normal menstrual cycle is the pointer of healthy and normal reproductive organ in which intermenstrual period is one month (Candramasa=28days), duration of menstrual blood flow is 5 days (differ acc. to different opinion of Acharyas) is not associated with pain or burning sensation, menstrual blood is not unctuous, not very scanty nor excessive in amount. Dysmenorrhoea is one of the common symptoms found in abnormal menstruation. Dysmenorrhoea means painful menstruation, it is a burning health problem now especially in post pubescent women in the age group of 18-25 years with ovulatory cycles due to today’s life style. That badly affects the daily routine activities and quality of life. Our ancient Ayurveda also describe it as Udavarta Yonivyapada, it is also found in many other disease of female as a symptom like Vatala Yonivyapada, Tridoshja Yonivyapada, Mahayoni, Vataja, Pittaja and Kaphaja Aartavadushti, Kunapagandhi Aartavadushti, Aartavakshaya, Vataja and Kaphaja Asrigdar. Modern medicine system have analgesics, antispasmodic and surgery for its treatment but all these have their own many more side effects which further gave trouble, but according to Ayurveda Basti Chikitsa has a very miraculous effect on dysmenorrhea in every reproductive age group without any further side effect. So we describe role of Basti Chikitsa in dysmenorrhea rest of the article.